(untitled) (Research, Society and Development, 2025)
This article analyzes the authenticity of feminist marketing and examines the tension between awareness-raising practices and purplewashing strategies that instrumentalize feminist discourse for commercial purposes. Through a theoretical review and a quantitative study applied to 162 participants, social perceptions about the veracity, impact and motivations behind campaigns that incorporate feminist narratives were evaluated. The results show a predominantly critical stance towards brands that use feminism superficially, as well as a moderate recognition of the transformative potential of feminist marketing when supported by coherent corporate actions. This study provides analytical elements to understand the public reception of the phenomenon and proposes criteria that allow us to differentiate genuine strategies from those that constitute purplewashing.